SS CRYNSSEN disembarking at Barbados - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
This photo shows a group of males assisting persons disembarking from the SS Crynssen cruise ship in Barbados in the year 1938. This method is used to take the passengers from the ship to land. These small boats used to transport passengers from cruise ships to port are called "tenders" because they are responsible for "tending" to the ship, ensuring passengers can safely disembark. This is a divided back postcard. Back of the Postcard: The number C1041 is printed at the back of the postcard PP £15 (Handwritten in pencil)
Landscape, Black and White, 3 ½” x 5 ½”
Keywords: Ships; Boats; Travel; Passenger ships